HD-tDCS to the lateral occipital complex improves haptic object recognition - Cacciamani, Laura; Tomer, Daniel; Mylod-Vargas, Mary Grace; Selcov, Aaron; Peterson, Grace A.; Oseguera, Christopher I.; Barbieux, Aidan (Experimental brain research, 2024)
High-definition transcranial direct current stimulation (HD-tDCS) is a non-invasive brain stimulation technique that has been shown to be safe and effective in modulating neuronal activity. The present study investigates the effect of anodal HD-tDCS on haptic object perception and memory through stimulation of the lateral occipital complex (LOC), a structure that has been shown to be involved in both visual and haptic object recognition. In this single-blind, sham-controlled, between-subjects study, blindfolded healthy, sighted participants used their right (dominant) hand to perform haptic discrimination and recognition tasks with 3D-printed, novel objects called “Greebles” while receiving 20 min of 2 milliamp (mA) anodal stimulation (or sham) to the left or right LOC. Compared to sham, those who received left LOC stimulation (contralateral to the hand used) showed an improvement in haptic object recognition but not discrimination—a finding that was evident from the start of the behavioral tasks. A second experiment showed that this effect was not observed with right LOC stimulation (ipsilateral to the hand used). These results suggest that HD-tDCS to the left LOC can improve recognition of objects perceived via touch. Overall, this work sheds light on the LOC as a multimodal structure that plays a key role in object recognition in both the visual and haptic modalities.